The development of grade one teachers' mathematics and pedagogical content knowledge through participation in a collaborative intervention - Mutlane, Kedisaletse Stella (Rhodes University, Faculty of Education, Department of Education)
The "South African education system is grossly inefficient, severely underperforming and egregiously unfair" (Spaull, 2013, p.3). In particular, grave concerns with learner performance in mathematics in South Africa are well documented (e.g., Taylor, 2008; Spaull, 2013; Venkat & Spaull, 2015). There are various explanations for the poor state of learner performance in mathematics in South Africa. Two of the explanations that relate closely to my research interest are teachers' insufficient mathematics content and pedagogical knowledge, and inappropriate professional development. This study aims to ascertain how a collaborative intervention can develop teachers' mathematics and pedagogical content knowledge as they focus on developing learners' foundational number sense. Cultural Historical Activity Theory, together with Mathematics Knowledge for Teaching (Ball et al., 2008) and the Knowledge Quartet (Rowlands & Turner, 2007) frameworks, provide the explanatory and analytic tools for the research. The research is a qualitative case study underpinned by an interpretivist orientation. The study was conducted at a township public primary school in the Northern Cape. Three Grade One teachers participated in the research. Data was collected through interviews, classroom observations, and videos of collaborative lesson planning and reflection sessions. A key finding emerging from this research is that the teachers had the necessary mathematics content knowledge to teach Grade One mathematics. Despite this and in contrast to it, they lacked adequate pedagogical content knowledge required to develop learners' number sense. To develop their pedagogical content knowledge, they required the intervention of a 'more knowledgable other' (Vygotsky, 2008). Several contradictions and tensions emerged from the research. For example, the teachers expressed that the opportunity to work collaboratively was beneficial, but it was evident that they were familiar with and accomplished in planning and working together. The contradictions emerging from this research provide an opportunity and basis for expansive learning for future collaborative teacher endeavours.
Keywords: Mathematics -- Study and teaching (Elementary) -- South Africa -- Northern Cape; Pedagogical content knowledge; Mathematics teachers -- Training of -- South Africa -- Northern Cape; Lesson planning -- South Africa -- Northern Cape; Teaching teams -- South Africa -- Northern Cape; Cultural Historical Activity Theory (CHAT)